APRENDIZAJE POR COMPETENCIA Y SU IMPACTO EN EL RENDIMIENTO ACADÉMICO DE LOS ESTUDIANTES. - HERRERA HOLGUIN EDWIN GERONIMO- (2024)
The following thesis deals with learning by competence and its impact on the academic performance of students, whose main objective is to determine learning by competence and its impact on the academic performance of third-year basic education students at the Juan E. Verdesoto in the area of mathematics. In which a research methodology with a mixed approach has been used, of an explanatory type trying to notice the effect on the research variables, with a descriptive- non-experimental design where investigative works were reviewed to gather information for said topic, aimed at a population. of 86 students from the Juan E. Verdesoto school corresponding to third-year students of basic general education, located in the province of Los Ríos, Babahoyo canton. With a sample of 38 students. The technique used for data collection is the survey and the instrument used in this research was the questionnaire, which provided us with valuable information in our research. Once the data was collected, they were tabulated, we selected the Excel statistical tool, obtained with instruments previously subjected to reliability and validity tests. The results have been statistically analyzed and showed a percentage of 80% of students who do not have the competency-based learning methodology, therefore they have difficulties in acquiring knowledge. Obtaining the conclusion that with the application of learning by competencies, academic performance is favored.